WANPRESTASI AKTA PERJANJIAN KERJASAMA YANG PIHAK PENJAMIN DALAM PENGAMPUAN (Studi Penetapan Pengadilan Negeri Kisaran No. 105/Pdt.P/2021/PN.Kis) - Irfan Hadi; Hasim Purba, Dedi Harianto, T. Keizerina Devi A. (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Default is a situation where a party is unable to fulfill its achievements to creditors in accordance with what was previously agreed. There are 3 (three) elements of breach of contract in Article 1243 of the Civil Code, namely the existence of an agreement, a party breaking their promise or violating the agreement, and has been declared negligent but still does not carry out the contents of the agreement. A person can be said to be in default in 4 (four) parts, namely if they do not fulfill the agreed achievements, fulfill the achievements inappropriately, fulfill the achievements not in accordance with the agreed time period and do things that are prohibited according to the agreed contract. The guarantor is a third party in the agreement whose job is to provide guarantees for the creditor's fulfillment of the debtor's achievements in accordance with what was agreed. Pardon is a condition where an adult person, because of his mental and physical condition, is placed under the supervision of another person who is legally competent. Guarantor who is in custody cannot be held accountable directly by the creditor, but can be asked to a third party appointed by the judge. This research method uses a Normative Juridical research type which is descriptive analytical in nature. The data source uses secondary data sources using legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials using library research data collection techniques (Library Research) and the data collection tools in this research are document studies and interviews. The results of the research show that the debtor was unable to fulfill his achievements to the creditor on time according to what had been previously agreed, and then the debtor died, so the responsibility for fulfilling the achievements shifted to the guarantor. The condition of the guarantor has deteriorated and is no longer cooperative since several months of the transfer of responsibility, so that responsibility is taken over by the guarantor's older brother (substitute guarantor), in which case the fulfillment of the achievement lasts 6 (six) years. The resolution of this case was through non-litigation settlement and litigation settlement. Fulfillment of achievements to creditors can be completed after the guarantor's collateral is sold by a replacement guarantor based on the Kisaran District Court's decision No.105/Pdt.P/2021/PN.Kis